Autocontrol procedures proposal on conservation of a road contracts (Gaceta Técnica, 2016)
With a mixed global contract the maintenance of a road network is carried out, through the simultaneous execution of conservation under the modality to series of unitary prices, and by sum raised by level of service. In the latter, there is a great precariousness in the procedures, due to failures in the contractor's vision of assuming the management of the conservation, lack in the assignment of responsibilities to the team members, and poor control in the work quality and documentation of the contract. For this reason, in this work a management proposal is made defining each of the stages that compose it, in order to ensure a correct conservation of the elements that make up the road infrastructure. The proposed objectives are: to specify the methodology to be used to manage the maintenance of the network contracted under the mixed global modality, to specify the handling and control of the documentation that must be kept in the contract, and to define the skills and responsibilities of the work team. In order to comply with them, a bibliographical revision of the national regulations on the maintenance of roads was carried out, and the diversity of contracts used by the Road Service for road conservation was taken into account. In addition, through experience in mixed global conservation contracts, the skills and responsibilities recommended by the members of the team are defined
Keywords: road network; conservation contract; self-control